The Human Glioma-Associated Oncogene Homolog 1 (GLI1) Family of Transcription Factors in Gene Regulation and Diseases - Zhu, Hu; Lo, Hui-Wen (Current Genomics, 2010)
Sonic hedgehog (Shh) signaling is critically important for embryogenesis and other cellular processes in which GLI transcription factors mediate the terminal effects of the pathway. GLI1, in particular, plays a significant role in human cancers. Consequently, GLI1 and its upstream positive regulator Smoothened (SMO) are important targets of anticancer therapy and several SMO-targeted small molecule inhibitors are being evaluated clinically. Emerging exciting evidence reveals a high level of complexity that lies within the GLI1-mediated pathway. For example, a recent study provided evidence linking the polymorphic GLI1 variants Q1100/E1100 to chronic inflammatory bowel diseases. Two recent reports uncovered the existence of two novel human GLI1 isoforms that differ structurally and functionally from the wildtype GLI1 identified over two decades ago. Interestingly, although both are products of alternative splicing, GLI1ΔN and tGLI1 (truncated GLI1) isoforms are predominantly expressed in normal and malignant tissues, respectively. In addition to these important discoveries, gene expression profiling studies have identified a number of novel wild-type GLI1 and tGLI1 target genes, linking wild-type GLI1 to tumor progression and therapeutic resistance, and tGLI1 to tumor invasion and migration. In light of these new insights, this review will provide a comprehensive overview on GLI1 polymorphisms and the three members of the GLI1 family of proteins, and their impacts on human diseases, including, cancers.
Keywords: polymorphism